International Conference “New Trends and Challenges in Management”.Treatment and Conclusions - Marzena Godlewska; Elżbieta Weiss (Contemporary Economics)
Process of integration create new challenges with European Union concerning principle function homogeneous market European and growth of competition from part of enterprise. It puts new claims before enterprises in range of preparation of venture, observances and business customs, taking into consideration of possessions of science or suitable creation firm image. However, globalization generates question of new culture of operation, with necessity of utilization of knowledge relate, in information society functioning and appearance new phenomena or instruments. World-wide trends and conversions extract strongest mark on functioning enterprise more. They were object of international scientific conference, that has proceeded in high school of finance and in Warsaw in November 2007.